2014
DOI: 10.1016/j.scitotenv.2014.01.047
|View full text |Cite
|
Sign up to set email alerts
|

A new optional recycled water pre-treatment system prior to use in the household laundry

Abstract: With a constantly growing population, water scarcity becomes the limiting factor for further social and economic growth. To achieve a partial reduction in current freshwater demands and lessen the environmental loadings, an increasing trend in the water market tends to adopt recycled water for household laundries as a new recycled water application. The installation of a small pre-treatment unit for water purification can not only further improve the recycled water quality, but also be viable to enhance the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The extracted wastewater undergoes physical separation processes to reduce suspended solids and attain a suitable quality level beneficial use [2]. These physical separation processes typically include multi-media filtration [6] and microfiltration (MF) [7] or ultrafiltration (UF) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The extracted wastewater undergoes physical separation processes to reduce suspended solids and attain a suitable quality level beneficial use [2]. These physical separation processes typically include multi-media filtration [6] and microfiltration (MF) [7] or ultrafiltration (UF) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that possible harmful microorganisms and chemical residues in recycled water pose a potential threat to human health, which has raised concerns about the safety of recycled water use (Gerrity et al, 2018). As a result, the public was reluctant to use recycled water due to health risks (Chen et al, 2014). Meanwhile, the loss of money and the inconvenience of subsequent maintenance receive less attention.…”
Section: Risk Perception Of Recycled Watermentioning
confidence: 99%
“…Material yang digunakan dalam penelitian ini adalah arang aktif tempurung lontar (Borassus flabellifer L.) (Lano, Ledo & Nitsae, 2020); (Nitsae, Solle, Martinus, & Emola, 2021), sabut kelapa (Pinandari, Fitriana, Nugraha, & Suhartono, 2011), pasir (Ahmad & El-Dessouky, 2008), dan zeolit (Chen et al, 2014. Semua material digunakan dalam sistem filtrasi yang dipilih sesuai fungsi masing-masing.…”
Section: Pendahuluanunclassified